Penerapan Metode Pembelajaran Kooperatif Tipe Numbered Head Together Dalam meningkatkan Hasil Belajar IPAS - Nurhidayah Nur; Aldino (Master of Civic Innovation and Education Technology, 2026)
Meaningful learning is inherently supported by various contributing factors, one of which is the learning model. Based on observations conducted by the researcher from April 6th to 11th, 2026, in Grade III at SD Negeri 155/II Tagan Senamat Ulu, Bungo Regency, it was found that the actual learning process in Science and Social Sciences (IPAS) showed a low level of student mastery, specifically regarding the material "Recognizing Surrounding Animals." This was evidenced by low exam scores and a lack of  student interest in the subject. Furthermore, the educator had not yet provided collaborative learning facilities for group discussions; for instance, the Numbered Heads Together (NHT) learning model had not been introduced. The delivery of material lacked variety and remained one-way, as the educator relied heavily on monotonous lecture and question-and-answer methods. The Numbered Heads Together (NHT) cooperative learning model is a group-based approach consisting of 4–5 students per group, where the educator assigns a number to each student. According to Shoimin, this type of research utilizes Classroom Action Research (CAR), which consists of four stages: planning, action, observing, and reflecting. Based on the research results, it can be concluded that the use of the Numbered Heads Together model in Grade III at SD Negeri 155/II Tagan Senamat Ulu improved both the learning process and outcomes. The improvement in the learning process, based on teacher observation sheet calculations, was recorded at 69.23% (Fairly Good) in Cycle I, Session I, and increased to 84.61% (Good) in Cycle I, Session II. The percentage reached 92.30% (Very Good) by Cycle II, Session I. Student learning outcomes also showed significant progress; in the post-test of Cycle I, only 17 students (65.38%) achieved the passing grade. However, in Cycle II, this increased to 23 students, thereby proving that the NHT model effectively enhances student learning outcomes.